KINERJA BADAN PERMUSYAWARATAN DESA KUMO KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA - WIDADARI, DENI FEIN; Rorong, Arie Junus; Londa, Very (Sam Ratulangi University, 2016)
Abstract : ACV Agency's consultative village is an institution which is a manifestation ofdemocracy in the Organization of the Government of the village. The function of the ACV is setting therules of the village along with the head of the village, as well as accommodating and channeling theaspirations of the community. Based on the existing realities of the villagers still belongs to the educationlevel of the Kumo and democracy at the village of Kumo can run well, it is affected by the performance ofthe Agency's consultative village (ACV) in organizing a Government of democratic Village in the village ofKumo, sub district of Tobelo, Halmahera Regency or Halmahera Utara.The problem in this research are (1) how does the exercise of the functions of Government in thevillage of ACV, (2) what are the obstacles faced by the Government in the village of ACV, (3) any effortsthat had been undertaken ACV to overcome barriers arising in organized governance. The purpose of thisresearch is (1) to know the implementation function of ACV, (2) to find out whether the obstacles faced bythe ACV, (3) to know what efforts had been made to overcome the existing barriers.Research methods used are qualitative research methods, data collection Methods used in thisresearch include observation, interview and documentation, to know the validity of the data by using thedata analysis technique performed with several stages, namely data reduction stage, the presentation of data,and the withdrawal of the conclusion or verification.The results showed, that the ACV has run both its functions properly. Barriers faced by ACV in theexercise of its functions caused by internal and external barriers, have been addressed positively by the ACV.Advice that can be given are (1) the need for cooperation between the Governments of North HalmaheraRegency with the Government to provide a supply of the village of ACV, (2) it needs to be a more adequatefunding allocation for the operational activities of ACV (3) the Government needs to consider the existenceof reward, namely in the form of allowances to the ACVKeywords: Village Government , Agency's consultative village